2020
DOI: 10.1155/2020/8894188
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cattle Trypanosomosis and Apparent Density of Its Fly Vectors in Bambasi District of Benishangul-Gumuz Regional State, Western Ethiopia

Abstract: Trypanosomosis is the most serious disease of cattle, which causes great socioeconomic losses in the country. Its socioeconomic impact is reflected on direct losses due to mortality, morbidity, and reduction in milk and meat production, abortion and stillbirth, and also costs associated with combat of the disease are direct losses. A cross-sectional study was carried out to assess the prevalence of cattle trypanosomosis, and the apparent density and distribution of its fly vectors in selected study areas. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Two species of trypanosomes were identified in the current study areas, namely, T. congolense (68.85%) and T. vivax (31.15%). This study has confirmed the observation of ( 8 , 13 , 16 , 17 , 49 ) in different parts of Ethiopia. The relatively higher predominance of T. congolense infection in cattle suggests the increased contact of cattle with the savanna tsetse flies, particularly G. pallidipes , which are more efficient transmitters of T. congolense than T. vivax in East Africa ( 12 , 50 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Two species of trypanosomes were identified in the current study areas, namely, T. congolense (68.85%) and T. vivax (31.15%). This study has confirmed the observation of ( 8 , 13 , 16 , 17 , 49 ) in different parts of Ethiopia. The relatively higher predominance of T. congolense infection in cattle suggests the increased contact of cattle with the savanna tsetse flies, particularly G. pallidipes , which are more efficient transmitters of T. congolense than T. vivax in East Africa ( 12 , 50 ).…”
Section: Discussionsupporting
confidence: 90%
“…The mean PCV of the infected animals (22.56 ± 4.61) was significantly (p < 0.001) lower than that of the noninfected ones (25.3 ± 4.75%). The lower mean PCV value in the infected animals have been reported by authors from different corners of the country (21,22,39,43,49). Variation between infected and non-infected animal mean PCV value indicates that trypanosomosis might be involved in the reducing of the PCV values in the infected animals (30).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Other caught biting flies were identified to genera level according to their morphological characteristics such as size, color, wing venation structure, and proboscis [ 26 – 28 ]. The apparent density of the tsetse fly was calculated as the number of tsetse catch/trap/day [ 29 ].…”
Section: Methodsmentioning
confidence: 99%